Mechanical strength and environmental impacts of eco-self-compacting mortar containing dune sand in the Oued-Souf region of Algeria as cementitious materials - Moussa Hadjadj; Youcef Toumi; Selma Lounis; Merouane Guettioui (Budownictwo i Architektura)
Desertification is a major global problem, while the scarcity of renewable energy sources continues to be a growing concern. Due to the abundance of dune sand in the southern regions of the Algerian Sahara, known as dry zones, and despite the beauty of the dune sand and its scenic appearance, it has become a threat to surrounding vegetation through the desertification of agricultural lands. To address these challenges, the use of dune sand as a cementitious material in sustainable concrete has been studied. In this work, the effect of using dune sand powder (DSP) as a partial replacement for Ordinary Portland Cement (OPC) on the workability, mechanical, and microstructural properties of self-compacting mortars (SCM) was investigated. In this study, OPC was replaced by 5%, 10%, 15%, and 20% DSP by weight. The fresh properties of SCM mixtures were evaluated using the mini-slump flow and V-funnel flow time tests. The mechanical performance of SCM was assessed through compressive strength and flexural strength tests. SEM analysis was also conducted to examine the microstructural development of the hardened SCM. The results show that the use of DSP improved the workability of SCM mixtures. The study revealed that the compressive strength and flexural strength increased to 63.03 MPa and 8.8 MPa, respectively, with a 20% DSP replacement. The findings demonstrate that up to 20% dune sand powder can be used as a Portland cement replacement, with a fineness of 5000 cm²/g, without adversely affecting mechanical performance. Despite its crystalline nature, dune sand powder exhibits partial pozzolanic reactivity.